Estimativa de demanda de energia elétrica em uma instituição de ensino superior. - Garcia, Altemir Tomaz de Carvalho (2015)
In recent years, several studies where published regarding to the estimation of variables related to the use of electricity, where the most varied methodologies are used to perform modeling and estimation of demand for energy of countries, States, companies in general and educational systems. In this dissertation where chosen this last category and the focus is on Higher Education Institutions (HEIs). Looking for drawing up an estimate of Wing Maxim Demand (WMD), monthly of electrical energy power, for the (HEIs), from the amount of students and, if necessary, from other causal variables, which can contribute to managerial way for the renegotiation of contracts with concessionaires that lead to annual cost savings and still contribute to a better control of the levels of maxim demand of electricity. To achieve this objective, it was realized a review of the literature regarding to the variables that could introduce correlation with the dependent variable WMD. This review indicated several methodologies that could contribute to the solution of the problem proposed: Markov Chain, Support vector Regression methodology, Genetic Programming Model and Artificial Neural Networks. It was adopted the methodology of Multiple Linear Regression (MLR) because it is less complex and a methodology directed at large companies. It was selected an IES and were carried out interviews with some engineers and technician of his electrical engineering division, seeking to better understand energy use and the behavior of the variable WMD in this IES being made available the reports of power energy monitoring where the WMD data of January-December 2008 of 2014 were contained. So on the basis of these data and documental research of the independent variables, and, through the methodologies of Multiple Linear Regression (MLR), it was developed a model from the data of 72 months which had their waste evaluated, showing a coefficient of determination R ^ 2 equal to 0.883. Independent variables that remained in the model, from the use of the backward method, were 4 (four) Dummy variables associated with the years, six variables of this type associated with the months and a variable which is the product of school days for graduates and the quantity of graduate students registered. This model was able to identify seasonality presents in the behavior of the WMD of this HIE. It would allow the hiring of WMD per month, that would make savings of 57% compared to the traditional contracting mode (WMD fixed for the entire period), considering the period from July to December, before the period left for validation. In conclusion, a forecast for the period of January to May 2015 and the adoption of the proposed model was able to provide a savings of 45% in relation to the scheme currently used by this HEI.